HSBC Trustee (CI) Limited v Kwong and Ors [2018] JRC051A. Issue 8 (28th July 2018) - Alexander, Stephen
Abstract: Data security incidents at financial institutions, law firms and trust and corporate service providers (including the 'Panama' and 'Paradise' articles) in recent times have renewed the discussion about the appropriate level of transparency of trusts and other private wealth structures. One aspect of this discussion turns on the manner by which applications by trustees for directions as to the administration of a trust should be reported by the courts. Should they be reported, as they traditionally have been in many jurisdictions, in an anonymized manner so as to preserve privacy of the trust and those connected to it, or should there be a greater emphasis on full and open publication of judgments? The Royal Court of Jersey's recently published judgment of HSBC Trustee (CI) Limited v Kwong and Ors [2018] JRC051A provides important guidance on the approach that the Jersey courts take in relation to the publication of judgments concerning such trustee directions applications.